Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) untuk Meningkatkan Aktivitas Belajar Peserta Didik Kelas X.3 SMA Negeri 5 Tanralili Maros - Kurniah Kurniah; Muhammad Danial; Ramdani Ramdani (Jurusan Kimia FMIPA UNM, 2021)
This research was a classroom action research (CAR). The aimed was to find systematic steps of TGT learning model to increase the activity of student in X3 grade of senior high school 5 Tanralili Maros. This research was conducted in two cycles. The results showed that the steps in each stage of the learning model that can improve student learning activities were: (1) The class presenting stage conducted by explained the objective learning and associated the learning topics that have been studied previously by orally to students, (2) the group discussion stage conducted by divided students into the learning heterogeneous groups, instructed students to master the topic at home, instructed students to bring reading topics that related to the subject of discussion and explained to students the meaning of teamwork, (3) the group presentation stage conducted by provided students to convey the results of the discussion and instructed students to make a questions before presentation time began, (4) the game stage conducted by instructed students to solve the problems independently and to uphold the values of honesty, (5) the tournament stage conducted by provided students to represent their group at the tournament table with same scores game, (6) the awards stage conducted by giving the prizes to the best groups and provided motivation to the group not as a winner in order to try harder, (7) the conclusions stage done by students and teacher together, which the students concluded the topic must be based on learning objectives. By implementing these stages, the students learning activities increased by 32.50 %.